Product design for students - Barker, Peter (Product designer) (Routledge, 2025)
"Product Design for Students covers the basic concepts and processes intrinsic to professional industrial product design: from the initial design concept through design for manufacture, sustainable production, distribution, marketing and recycling of the product at the end of its life. Concept generation techniques, design process methodologies, the use of design thinking, user centred design and co-design, design for sustainable production, materials and manufacturing process selection, quality control, design for recycling, marketing and distribution are all covered at an introductory level. Case studies and examples from transport design, consumer product design and service design projects are all included in this book. Product design is for anyone with sufficient interest, from beginners to advanced students. No background is necessary to engage with this exciting book. It serves as an introduction to the subject for those who might be looking to make a career as a product designer or who need to understand the profession as a career advisor or on a collaborative and managerial basis"-- Provided by publisher.